Reentry spontaneous pneumomediastinum at high altitude: a two-case report - Lopez de Guimaraes, Douglas (2022)
We describe two cases of spontaneous pneumomediastinum (SPM) that occurred in healthy, high-altitude native adolescent males when returning to their home from sea level. Both attended the Emergency Department of the Hospital Víctor Ramos Guardia in Huaraz, Ancash (3,052 m a.s.l.), in February 2020. Case 1 was a 16-year-old man who returned home (2,964 m a.s.l.) after twelve days at sea level (Lima). Six hours after returning, he went to work in the field. He then presented fatigue, cough, chest pain, dyspnea, and subcutaneous emphysema. Case 2 was a 17-year-old man who returned home (3,140 m a.s.l.) two weeks after staying at sea level (Barranca). Twelve hours after returning, he went to work in the field. He then presented cough, dyspnea, chest pain, sore throat, and subcutaneous emphysema. Both patients developed hypoxemia, and SPM was diagnosed with the help of chest X-rays. Case 2 was associated with mild high-altitude pulmonary edema. Both patients had no previous history of trauma, illicit drug use, comorbidity, and high-altitude-related diseases. Disease management was conservative, symptomatic, supportive, and based on clinical observation. When a healthy young patient comes to an emergency department because of chest pain, dyspnea, and subcutaneous emphysema, we should consider the possibility of SPM and immediately request frontal and lateral chest X-rays that include the cervical region. A differential diagnosis enables physicians to provide adequate and accurate treatment to patients with SPM.